Towards a global framework for assessing male involvement in maternal health: results of an international Delphi study - Kristien Roelens; Sally Griffin; Anna Galle; Nafissa Osman; Olivier Degomme (BMJ Open)
Purpose Currently, no standard instrument exists for assessing the concept of male involvement in maternal health, hampering comparison of results and interpretation of the literature. The aim of this study was to construct the key elements of a global multidimensional male involvement framework, based on the latest evidence and input of experts in the field.Methods For this purpose, a Delphi study, including an international panel of 26 experts, was carried out. The study consisted of three rounds, with 92% of respondents completing all three surveys. Experts were asked to rate indicators within six categories in terms of validity, feasibility, sensitivity, specificity and context robustness. Furthermore, they were encouraged to clarify their rating with open text responses. Indicators were excluded or adapted according to experts’ feedback before inclusion. A 85% agreement was used as threshold for consensus.Results A general consensus was reached for a global framework for assessing male involvement in maternal health, consisting of five categories: involvement in communication, involvement in decision-making, practical involvement, physical involvement and emotional involvement.Conclusions Using the male involvement framework as a tool to assess the concept of male involvement in maternal health at local, national, and international levels could allow improved assessment and comparison of study findings. Further research is needed for refining the indicators according to context and exploring how shared decision-making, gender equality and women’s empowerment can be assessed and facilitated within male involvement programmes.